1968
DOI: 10.1128/mmbr.32.2.103-126.1968
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-sensitizing factors from microbial agents, with special reference to Bordetella pertussis.

Abstract: a Toxicity = LD5so of histamine given intraperitoneally, expressed as milligrams of histamine base per kilogram of body weight. b J. Munoz, unpublished data. toxin. This reaction was most probably an anaphylactic shock, although it was not recognized as such by Ospeck and Roberts. Parfentjev et al. (186-188) observed a similar phenomenon when they found that mice pretreated with pertussis vaccine died after receiving a denatured nucleoprotein isolated from B. pertussis. This sensitivity was considered to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…It was revealed that purified LPF consisted solely of uniform filamentous molecules of about 2 by 40 nm. (16), including leucocytosis. Recently, Morse et al (11,12,14,15) studied the mechanisms involved in development of leucocytosis in mice injected with pertussis cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that purified LPF consisted solely of uniform filamentous molecules of about 2 by 40 nm. (16), including leucocytosis. Recently, Morse et al (11,12,14,15) studied the mechanisms involved in development of leucocytosis in mice injected with pertussis cells.…”
Section: Resultsmentioning
confidence: 99%
“…The injection of killed PO in humans and animals produces numerous biological phenomena. In mice, leukocytosis, splenomegaly, increase in sensitivity to agents such as histamine or serotonin, induction of nonspecific resistance to infection, potentiation of tumor defense mechanisms, and adjuvant activity are the most prominent features (8,22). Recent studies (H. Hof et al, submitted for publication) have shown that the time interval between the PO injection and the infection with L. monocytogenes is of crucial significance for increased resistance to L. monocytogenes.…”
Section: Infect Immunmentioning
confidence: 99%
“…After injection ofB. pertussis, mice and rats which are normally resistant to the lethal effects of histamine become highly sensitive (4)(5)(6)(7). Histamine-sensitizing factor (HSF) activity was assayed in pertussis-treated mice by injecting the equivalent of 1 mg of histamine-free base, as histamine dihydrochloride (sehwarz/Mann Div., Becton, Dickinson & Co., Orangeburg, N.…”
Section: Biological Assaysmentioning
confidence: 99%